Return-to-Work Management in A Palm Oil Harvester with Occupational Keratitis from A Foreign Body: A Case Report - Mardiansyah Kusuma; Dewi Sumaryani Soemarko (The Indonesian Journal of Community and Occupational Medicine, 2025)
Introduction: Effective return-to-work (RTW) management is essential for minimizing workplace disruptions and supporting functional recovery following occupational injuries. In physically demanding sectors such as palm oil harvesting, eye injuries—particularly occupational keratitis caused by plant debris—can lead to temporary visual impairment and reduced ability to perform essential job tasks. Objective.This case report demonstrates how structured RTW coordination, involving interprofessional collaboration and employer engagement, facilitates safe workplace reintegration and prevents reinjury.Methods: We report the case of a 27-year-old male palm oil harvester in Indonesia who developed left-eye keratitis after removing fogged protective goggles during harvesting. He was treated by an ophthalmologist, while a hospital-based occupational medicine specialist—acting in place of an internal occupational health unit—evaluated his work capacity, recommended temporary duty adjustments, and collaborated with company management to implement them.Results: Initial treatment consisted of topical antibiotics and ocular lubricants. The patient was deemed temporarily unfit for regular duties and was advised to perform low-risk tasks. Although the employer’s response was initially delayed, collaboration with the occupational physician facilitated a phased return to work through modified duties and ongoing monitoring. Full visual recovery was achieved within 17 days, after which the patient resumed regular tasks without restrictions. At 3.5 months post-injury, he remained asymptomatic and fully fit for work.Conclusions: Successful return to work (RTW) following occupational keratitis requires early and structured coordination between ophthalmologists and occupational medicine specialists, as well as active involvement from the employer. Temporary job modifications, functional capacity assessments, and ongoing monitoring are essential to ensure a safe reintegration process and to maintain productivity. In the absence of on-site occupational health services, hospital-based occupational medicine specialists play a vital role in conducting fitness-for-work evaluations and recommending appropriate workplace accommodations.